Forbidden From Getting Sick And Being Literate? Health Care And Education Opportunities For Undocumented Migrant Workers In Asia - Maharani, Shinta; Ab Rahman, Asmak; Mohd Noh, Mohd Shahid (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
Migrant workers are considered vulnerable as they remain excluded from various social safety provisions. The Covid-19 pandemic has further exposed significant gaps in policy support for these workers in Asian countries. However, scholarly evidence is lacking in the international literature to guide policy, particularly on undocumented workers. This paper fills this void by critically reviewing emerging evidence on undocumented migrant workers' access to healthcare and formal education in Asian countries according to a comprehensive analysis of research papers released between 2002 and 2022. In total, 72 scientific papers were identified from Scopus, WoS, and Emerald databases. The qualitative research software Nvivo was used to analyze the final 10 studies (out of 72 indexed articles). The findings of the review exercise suggest that the government should develop policies and solutions for undocumented migrant workers to get healthcare and formal education opportunities.